Empires of vice: the rise of opium prohibition across Southeast Asia - Kim, Diana S. (Histories of economic life, 2020)
A Shared Turn : Opium and the Rise of Prohibition -- The Different Lives of Southeast Asia's Opium Monopolies -- "Morally Wrecked" in British Burma, 1870s-1890s -- Fiscal Dependency in British Malaya, 1890s-1920s -- Disastrous Abundance in French Indochina, 1920s-1940s -- Colonial Legacies.